Effect of Dimensionality on The Electronic Properties of SnSe: A Density Functional Theory Study - Fatimah Arofiati Noor; Erik Bhekti Yutomo; Toto Winata (Institut Teknologi Bandung, 2021)
This study investigated the structural and electronic properties of bulk, bilayer, and monolayer SnSe using the density functional theory (DFT) method. We succeeded in calculating the bandgap and identifying accurately the transformation of the band structure from bulk to monolayer systems using generalized gradient approximation. An increase in the lattice parameter a and a decrease in the lattice parameter b were observed when the bulk dimensions were reduced to a monolayer. The reduction of van der Waals interactions when the dimensions of a system are reduced is the main factor that causes changes in lattice parameters. The indirect bandgap of bulk SnSe (0.56 eV, 0.3∆→0.7Σ) becomes wider in the monolayer system (0.94 eV, 0.2∆→0.8Σ). Bandgap widening is predicted due to the emergence of the quantum confinement effect in low-dimensional systems. Furthermore, we found the formation of a quasi-degenerate minimum conduction band in the monolayer SnSe. With the formation of these bands, we predict the monolayer SnSe will have better thermoelectric properties than the bulk or bilayer system. This study provides an in-depth understanding of the electronic structure of SnSe and its correlation to thermoelectric properties.